Right diaphragmatic hernia after liver transplant in pediatrics: A case report and review of the literature. (26th February 2013) - Lam, Hwai‐Ding; Mejia, Juan; Soltys, Kyle A.; Sindhi, Rakesh; Mazariegos, George; Bond, Geoffrey
Abstract Diaphragmatic hernias (DH) are an unusual complication after pediatric liver transplantation; however, they have been reported with increased frequency in the past few years. DHs are responsible for nearly half of the small bowel obstructions requiring surgical intervention in this patient population. It has been suggested that the use of a left lobe liver graft, surgical trauma, malnourishment, elevated intra‐abdominal pressures, and mTor inhibitors may predispose to development of DH. The use of a segmental graft may increase the recognition of diaphragmatic hernia because the surgically damaged right hemi‐diaphragm often remains exposed to underlying viscera, instead of being covered by the right hepatic lobe. Treatment is surgical reduction, with up to 20% of the patients requiring resection of the herniated intestine. Herein we describe a case of DH after left segmental liver transplant in a two‐ yr‐old boy that presented one month post left lobe split liver transplant with abdominal pain, anorexia, and respiratory distress. Just like in the majority of the reported cases, an urgent laparotomy with primary repair was performed. No resection of the herniated segment of intestine was required. For pediatric patients with otherwise unexplained respiratory or gastrointestinal symptoms after a left lateral segment liver transplant, right‐sided diaphragmatic hernias should always be high in the differential diagnosis.